Pertinencia constitucional de las ordenanzas aprobadas en el gobierno autónomo descentralizado municipal de Guaranda durante el período 2020-2021 - Valle Oñate, Geovanna Lucía (2023)
Constitutional Courts have a reactive role in the control of constitutionality. This condition leaves constitutional self-protection a secondary role. In this way, the legislative bodies of decentralized autonomous governments (GADM) frequently or possibly generate ordinances over which there is no control of relevance (normative guarantee), until their results end in violations of the constitutional norm. This paper raises the urgency of constitutional self-tutelage in the decentralized autonomous governments of Ecuador in order to review the relevance of the ordinances approved in the Cantonal Council of the GADM of Guaranda during the period 2020-2021. For this purpose, it suggests a measurement of form and substance. The main finding is the weak normative construction as a response to the respect of the fundamental rights set out in the Constitution.